Perlindungan Hukum Bagi Pemegang Surat Utang Negara Atas Risiko Gagal Bayar (Default) - Heriyanto Heriyanto (Perspektif Administrasi Publik dan hukum, 2025)
Public enthusiasm for government bonds is high due to the view that such investments are considered more saving and promising. In 1950 the government issued ORI with interest of 3% per year, but the bonds failed to pay because the government at that time did not have enough money so that many investors holding bonds as Government Debt Instruments experienced losses. In this research, a juridical analysis of the position of the parties in Government Debt Instruments (SUN) was carried out and an analysis of the form of legal protection for holders of Government Debt Instruments (SUN) in the risk of default provided by the government. The research method used in writing this law is normative juridical, with a statutory approach. There are findings that installments of principal and interest on state debt securities will be included as expenditure items in the APBN each year. In the event that the risk of default does not sever the civil relationship between the SUN Issuer and the SUN holder as an Investor in a civil relationship, investors who suffer losses based on their civil rights can file a lawsuit for default due to the risk of default.